Colorectal Secondary Malignancy Risk Estimates Following Radiation Therapy: A Prospective Cohort Study Among Cancer Survivors In Saudi Arabia - Djouider, Fathi; Abolaban, Fouad (Journal of King Abdulaziz University: Engineering Sciences, 2024)
Radiation-induced second cancer is one of the crucial late side effects of radiotherapy treatment of first cancer. Although the second cancer induction mechanism is not well understood yet, many factors are related to its occurrence, such as age at exposure, dose to the organ and surrounding tissues, treatment modalities, and family history of cancer. This study aims to provide long-term estimates of second cancer incidence amongst colon cancer survivors in Saudi Arabia. The lifetime attributable risk (LAR) after radiation treatment of colon cancer was determined, between the age at exposure and up to 95 years, in a single-institution cohort of male and female cancer survivors whose age at treatment was in the range of 43 to 85 years. Risk estimates varied significantly with age at exposure, gender, and organ dose.